DO/ART4 gene sequencing in sub‐Saharan cohorts and African migrants: useful data describing the diversity and spreading of rare variants - (:unkn) unknown (My University, 2019)
Due to the unavailability of immunological reagents, the Dombrock blood group is insufficiently explored in African populations and can be a source of alloimmunization. A large study including pygmoid and nonpygmoid ethnic groups from East, Central, and West continental Africa, together with African migrants like Comorians, Afro-Caribbean from Martinique, and Maroons from French Guiana would be helpful to increase transfusion safety.
Keywords: African Research